2021
DOI: 10.1002/anie.202102657
|View full text |Cite
|
Sign up to set email alerts
|

High‐Rate CO2 Electroreduction to C2+ Products over a Copper‐Copper Iodide Catalyst

Abstract: Electrochemical CO2 reduction reaction (CO2RR) to multicarbon hydrocarbon and oxygenate (C2+) products with high energy density and wide availability is of great importance, as it provides a promising way to achieve the renewable energy storage and close the carbon cycle. Herein we design a Cu‐CuI composite catalyst with abundant Cu0/Cu+ interfaces by physically mixing Cu nanoparticles and CuI powders. The composite catalyst achieves a remarkable C2+ partial current density of 591 mA cm−2 at −1.0 V vs. reversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
131
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(134 citation statements)
references
References 40 publications
3
131
0
Order By: Relevance
“…In addition to doping, halogen ions adsorbed on the surface of copper can also promote the stability of Cu + . [127][128][129][130][131] Cu cubes derived from CuCl are a classic example. It was observed that a certain amount of Cu + in the Cl-containing precursor was stable in the CO 2 RR catalysis process.…”
Section: Adsorption Strength Regulationmentioning
confidence: 99%
“…In addition to doping, halogen ions adsorbed on the surface of copper can also promote the stability of Cu + . [127][128][129][130][131] Cu cubes derived from CuCl are a classic example. It was observed that a certain amount of Cu + in the Cl-containing precursor was stable in the CO 2 RR catalysis process.…”
Section: Adsorption Strength Regulationmentioning
confidence: 99%
“…Ag, Au, and Pd) electrocatalysts, and Fe, Co and Ni-based single-atom catalysts (SACs) have been reported to be active in the CO 2 RR to produce CO, 19–21 their commercialization was impeded by the high cost, limited reserves of noble metals and the difficulty of large scale preparation of SACS. 22–31 Thus, it is still urgently desirable to develop highly efficient robust catalysts to improve the performance for the CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Theh igh-value multicarbon (C 2+ )h ydrocarbons products via CO 2 reduction reaction (CO 2 RR) are highly attractive due to their practical applications; [2] however, their selectivity and activity are severely limited by multistep hydrogenation steps and competitive reactions. [3] Copperbased material is the most efficient electrocatalyst for selectively converting CO 2 to C 2+ products, [4] and its performance can be further influenced via modulating oxidation states, [5] grain boundaries [6] and unsaturated sites. [7] Itsworth noting that these structural features of copper-based material can be in situ changed due to the precatalyst reconstruction under CO 2 RR conditions.T aken copper oxides as ac lassic example,t hey usually act as CO 2 RR precatalysts,w hich can be partially reduced to regenerate biphasic copper/copper oxide,c oupled with abundant grain boundaries and unsaturated sites as active CO 2 RR species,e xhibiting significantly increased CO 2 RR performance than the pure copper.…”
Section: Introductionmentioning
confidence: 99%